letter to the editor about a published article DOI: 10.2196/mhealth.8458 - Johan Goris (2017)
Background Breast cancer and its treatment can negatively affect women's quality of life (QoL), including physical, psychological, and social well-being. Digital health interventions have been increasingly used to provide supportive care, but their effectiveness on QoL and related psychosocial outcomes remains unclear. Objective This review aimed to evaluate the effectiveness of digital health interventions on QoL in women with breast cancer and to assess their effects on anxiety, depression, and self-efficacy. Methods This systematic review was registered in PROSPERO (CRD420250578307) and conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) 2020 statement. PsycINFO, Web of Science, Scopus, LILACS, and SciELO were searched in September 2025. Eligible studies were randomized controlled trials (RCTs) or controlled quasi-experimental studies with preintervention and postintervention assessments that evaluated digital health interventions in women with breast cancer during or up to 1 year after active treatment and reported QoL outcomes. Two reviewers independently screened all records (interrater agreement >90%) and extracted data using a standardized template, with independent verification by a second reviewer. Risk of bias was assessed using the Cochrane Risk of Bias tool (RoB 2) for RCTs and the Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I) tool for the quasi-experimental study; findings were synthesized narratively following the Synthesis Without Meta-analysis (SWiM) guideline. Results A total of 408 records were identified, and 15 studies were included: 14 RCTs and 1 quasi-experimental study. Sample sizes ranged from 35 to 394 participants. Ten studies evaluated internet-based approaches such as websites or apps; 3 used text messaging (eg, WhatsApp [WhatsApp LLC] or WeChat [Tencent Technology, Shenzhen Company Limited]), 1 used virtual reality, and 1 used an email listserve. The direction of effect favored the digital intervention for QoL in 8 of the 15 studies. Self-efficacy was assessed in 5 studies and favored the intervention in only 1, with the effect not maintained at follow-up. Anxiety, depression, or emotional distress were assessed in 13 studies, with a favorable direction of effect in 5. Retention rates ranged from 68.6% to 100%. Among the 14 RCTs, 3 were judged at high overall risk of bias, and 11 raised some concerns; none was at low risk. The quasi-experimental study had a serious overall risk of bias. Certainty of evidence was low for QoL and emotional outcomes and very low for self-efficacy. Conclusions Digital health interventions may provide modest, short-term improvements in some dimensions of QoL in women with breast cancer. Favorable effects appeared more often in interventions with active therapeutic components or professional support; however, this pattern was based on indirect comparisons across heterogeneous studies. Effects on self-efficacy and mental health were inconsistent, and acceptability was insufficiently evaluated. Although promising, current evidence does not support strong or generalizable conclusions.